2011
DOI: 10.1002/dev.20538
|View full text |Cite
|
Sign up to set email alerts
|

Personality variation in a clonal insect: The pea aphid,Acyrthosiphon pisum

Abstract: Individuals are often consistent in their behavior but vary from each other in the level of behavior shown. Despite burgeoning interest in such animal personality variation, studies on invertebrates are scarce, and studies on clonal invertebrates nonexistent. This is surprising given the obvious advantages of using invertebrates/clones to tackle the crucial question why such consistent behavioral differences exist. Here we show that individuals of clonal pea aphids exhibit consistent behavioral differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 64 publications
6
90
0
1
Order By: Relevance
“…Genetically identical offspring of the facultatively asexual aphid Acyrthosiphon pisum display surprising variability in their predator avoidance behaviors, a phenomenon that may help the aphid population escape a variety of insectivores (46). Similarly, a quantitative analysis of locomotion in Aphis fabae, another clonal aphid, suggested that individual insects display idiosyncrasy in their food-foraging behaviors (47).…”
Section: Discussionmentioning
confidence: 99%
“…Genetically identical offspring of the facultatively asexual aphid Acyrthosiphon pisum display surprising variability in their predator avoidance behaviors, a phenomenon that may help the aphid population escape a variety of insectivores (46). Similarly, a quantitative analysis of locomotion in Aphis fabae, another clonal aphid, suggested that individual insects display idiosyncrasy in their food-foraging behaviors (47).…”
Section: Discussionmentioning
confidence: 99%
“…The idiosyncratic behavior of each fly was partially preserved (i.e., dark-preferring flies remained darkpreferring) over at least 4 wk, essentially a fly lifetime. Thus, VBE can be interpreted as phototactic "personality" [sensu (1)]. …”
Section: All Strains Exhibit More Behavioral Variability Than Expectementioning
confidence: 99%
“…Behavioral individuality, in the absence of genetic variation, has indeed been observed in the laboratory. Specifically, clonal pea aphids were shown to vary in their predator escape behavior, and these differences were maintained for at least 5 d (1). In another example, the naïve odor preference of fruit flies was highly variable across individuals (2).…”
mentioning
confidence: 99%
“…More studies are now desirable that investigate whether behavioral differences induced by developmental effects are consistent and stable, i.e., whether environmental conditions experienced influence animal personalities. Indeed, there is an increasing number of studies focusing on the development of animal personality (e.g., Sinn et al, 2008;Brodin, 2009;Schuett et al, 2011a;Gyuris et al, 2012;Hedrick and Kortet, 2012;Niemelä et al, 2012b;Petelle et al, 2013;Sweeney et al, 2013;Tremmel and Müller, 2013;Guenther et al, 2014;Johnson et al, 2015). To clearly identify underlying processes, experimental studies in which environmental conditions are manipulated are needed.…”
Section: Introductionmentioning
confidence: 99%